The genome of woodland strawberry (Fragaria vesca) - Shulaev, Vladimir; Sargent, Daniel J; Crowhurst, Ross N; Mockler, Todd C; Folkerts, Otto; Delcher, Arthur L; Jaiswal, Pankaj; Mockaitis, Keithanne; Liston, Aaron; Mane, Shrinivasrao P; Burns, Paul; Davis, Thomas M; et al. (Nature genetics, 2011)
The International Strawberry Sequencing Consortium reports the draft genome of the woodland strawberry ( Fragaria vesca ). The genome of this diploid species should serve as a reference genome for the Fragaria genus, as the cultivated strawberry ( Fragaria × ananassa ) is an octoploid where F. vesca is predicted to be a subgenome donor. The woodland strawberry, Fragaria vesca (2 n = 2 x = 14), is a versatile experimental plant system. This diminutive herbaceous perennial has a small genome (240 Mb), is amenable to genetic transformation and shares substantial sequence identity with the cultivated strawberry ( Fragaria × ananassa ) and other economically important rosaceous plants. Here we report the draft F. vesca genome, which was sequenced to ×39 coverage using second-generation technology, assembled de novo and then anchored to the genetic linkage map into seven pseudochromosomes. This diploid strawberry sequence lacks the large genome duplications seen in other rosids. Gene prediction modeling identified 34,809 genes, with most being supported by transcriptome mapping. Genes critical to valuable horticultural traits including flavor, nutritional value and flowering time were identified. Macrosyntenic relationships between Fragaria and Prunus predict a hypothetical ancestral Rosaceae genome that had nine chromosomes. New phylogenetic analysis of 154 protein-coding genes suggests that assignment of Populus to Malvidae, rather than Fabidae, is warranted.